CONTRABAND: IMPACT ON MARITIME SECURITY IN MALACCA STRAITS - Zahimi Zainol Abidin; Mohd Farid Ikhwan Adinan; Noor Azmi Haji Mohd Zainol (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Objective - The existence of contraband domestically has to be thoroughly studied through comprehensive research on the definition of contraband, application of the law, the occurrences of smuggling activities, impact on domestic and border security which will include economic and reasonable preventive and mitigation measures to be considered. Thus, the research aims to investigate and analyse the severity of contraband related to smuggling activities on maritime security in the Malacca Straits. Methodology/Technique - Study to employ Nursing Theory in identifying various aspects of contraband which can be broken down into 3 aspects: Nature and extent of contraband, impact on maritime security and preventive measures. Primary data are gathered through journals, reports and articles. The study will then come up with a comprehensive conclusion on contraband. Finding - Study will provide a comprehensive understanding on contraband which will include the definition of contraband, impact of contraband on various aspects and the measures to be considered in controlling contraband. However, the measures to be considered will be the ideas for others to be kept as consideration in formulating law and action by the enforcement agencies. Novelty - The findings and outcomes of the study showed the reality of contraband existence and threat towards maritime security in Malacca Straits is still exist. As a result, new proactive measures to be considered in order to contain the situation. Type of Paper: Empirical